2019
DOI: 10.1002/adma.201906115
|View full text |Cite
|
Sign up to set email alerts
|

Passivating Detrimental DX Centers in CH3NH3PbI3 for Reducing Nonradiative Recombination and Elongating Carrier Lifetime

Abstract: After a period of rapid, unprecedented development, the growth in the efficiency of perovskite solar cells has recently slowed. Further improvement of cell efficiency will rely on the in‐depth understanding and delicate control of defect passivation. Here, the formation mechanism of iodine vacancies (VI), a typical deep defect in CH3NH3PbI3 (MAPbI3), is elucidated. The structural and electronic behaviors of VI are like those of a DX center, a kind of detrimental defect formed by large atomic displacement. Aide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 66 publications
2
54
0
Order By: Relevance
“…Recently, Wang et al 54 found that the structural and electronic characteristics of VI − in MAPbI3 are similar to the DX in tetrahedral semiconductor, which is a harmful defect caused by a large atomic displacement, as shown in Fig. 4d-f.…”
Section: Point Defects Passivationmentioning
confidence: 87%
“…Recently, Wang et al 54 found that the structural and electronic characteristics of VI − in MAPbI3 are similar to the DX in tetrahedral semiconductor, which is a harmful defect caused by a large atomic displacement, as shown in Fig. 4d-f.…”
Section: Point Defects Passivationmentioning
confidence: 87%
“…Some researchers believe that the iodine vacancies (V I ) are shallow donors, [56,57,59] but Agiorgousis and a recent study by Wang et al revealed that V I formed deep-level traps by inducing the generation of lead dimers. [60][61][62] Iodine interstitial (I i ) defects were identified as shallow acceptor in the studies of Yin et al [56] In contrast, the further calculation by Du's et al showed that among all point defects, only the I i was deep carrier traps and non-radiative recombination centers. [63,64] Similar discrepancies also occurred in the Pb interstitial (Pb i ) and the two anti-site defects I MA and Pb MA .…”
Section: Intrinsic Point Defectsmentioning
confidence: 99%
“…Small DE g (less than 0.10 eV) does not have a significant impact on the optical properties and could facilitate electron-hole separation to avoid fast recombination, leading to longer carrier lifetime. For example, the recombination rate of photogenerated electrons and holes slowed down in hybrid organicinorganic perovskite CH 3 NH 3 PbI 3 because of the phonon-assisted process in indirect bandgap [66,67].…”
Section: Electronic and Optical Propertiesmentioning
confidence: 99%